Status of Oxidative Stress, Antioxidants and Liver Function Tests among Nepalese Workers from Gulf Countries and Malaysia - Sharma, Abha; Shrestha, Vikram; Paudel, Govinda; Prajapati, Asmita (International Journal of Occupational Safety and Health, 2025)
Introduction: Nepalese migrants to the Gulf countries and Malaysia are prone to poor health because of their low status as migrants, challenging living and working conditions, changes in lifestyle, and inadequate access to health care. The main aims of this study were to assess the status of oxidative stress, antioxidants, and liver function among Nepalese workers from Gulf countries and Malaysia. Methods: A descriptive cross-sectional study was conducted among 332 Nepalese migrant workers to Gulf countries and Malaysia arriving at Tribhuvan International Airport during May 15 and June 15, 2019. Data was collected using a structured questionnaire, anthropometric measurements, and venous blood sample to access the status of oxidative stress, antioxidants, and liver function. Blood samples were analyzed at the laboratory of Janamaitri Foundation Institution of Health Sciences. Results: Results revealed that 5% had an abnormal liver panel test. The mean value for Serum Malondialdehyde (MDA) was 1.57± 1.25 µmol/L while 38.8% had an increased level of MDA. The mean value for total Protein was 7.19 ± 0.97 gm %, albumin was 4.43 ± 0.75 gm %, and Albumin/ Globulin Ratio was 1.8. There was a significant difference in MDA, SOD, and A/G ratio among migrant workers as per country of work. Conclusion: Nepalese migrant workers in Gulf countries and Malaysia are vulnerable to developing liver diseases. The high levels of serum MDA among Nepalese migrant workers is an important concern for the health care system. Thus, strengthening policy for regular health screening among these migrant workers is warranted.